2014
DOI: 10.1080/01425692.2014.916603
|View full text |Cite
|
Sign up to set email alerts
|

Learning active citizenship: conflicts between students’ conceptualisations of citizenship and classroom learning experiences in Lebanon

Abstract: Education for active citizenship continues to be a critical response for social cohesion and reconstruction in conflict-affected areas. Oftentimes, approaches to learning and teaching in such contexts can do as much harm as good. This study qualitatively examines 435 students' reflections of their civics classroom learning experiences and their existing conceptualisations of good citizenship. The majority of students revealed notions of citizenship representing high levels of engagement in community-building a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…However, the dominant didactic learning and teaching practices in Lebanese schools (Shuayb, 2007), particularly civics (Akar, 2012(Akar, , 2014 and history (Abouchedid et al, 2002) classrooms, undermine the intention to engage learners in dialogic activities. In civics classrooms, where teachers and students most commonly address topical and sensitive issues, teachers often steer away from debates and discussions in fear of emotional repercussions (Akar, 2012).…”
Section: Developing Dialogic Pedagogy In Education In Lebanonmentioning
confidence: 97%
“…However, the dominant didactic learning and teaching practices in Lebanese schools (Shuayb, 2007), particularly civics (Akar, 2012(Akar, , 2014 and history (Abouchedid et al, 2002) classrooms, undermine the intention to engage learners in dialogic activities. In civics classrooms, where teachers and students most commonly address topical and sensitive issues, teachers often steer away from debates and discussions in fear of emotional repercussions (Akar, 2012).…”
Section: Developing Dialogic Pedagogy In Education In Lebanonmentioning
confidence: 97%
“…Alanyazında etkin vatandaşlık konusunda öğretmen görüşlerini ve Sosyal Bilgiler dersinde yaşanan sorunları ele alan (Ersoy, 2007;Ersoy, 2014;Kara vd., 2012); etkin vatandaşlığın sınıf içinde öğretimini ortaya koyan ve öneri getiren (Akar, 2016;Hablemitoğlu ve Özmete, 2012;Keser, Akar ve Yıldırım, 2011;Sharma, 2015;Smith ve Graham, 2014); sivil toplum kuruluşları bağlamında etkin vatandaşlığı inceleyen (Çakmaklı, 2015;Edwards vd., 2015) çalışmalar bulunmaktadır. Çatışma çözme sürecini ise genellikle alanyazında deneysel yöntemlerle ele alan çalışmalar (Mutlu ve Serin, 2012;Gündoğdu, 2009;Gürdoğan Bayır, 2015;Türnük vd., 2009, Erem, 2008Sünbül, 2008;Zengin, 2008, Sarı, 2005Burnes, 2007;Catterall, 2007;Mayorga, 2005;Warner, 2005) bulunmaktadır.…”
Section: Etkin Vatandaşlık Boyutlarıunclassified
“…In the survey packs that 435 students in grades 10 and 11 completed (Akar ), 44.7 per cent placed ‘knowing the history of the country’ among the bottom three spaces of a nine‐part diamond ranking exercise. The students' written comments near the most and least important showed that their concerns lie mainly with the condition of history education in Lebanon.…”
Section: Researching Citizenship Education In Lebanonmentioning
confidence: 99%
“…Through semi‐structured interviews, teachers reflected on their understandings of citizenship, aims of citizenship education and classroom teaching experiences (Akar ). The students, from grades 10 and 11 civics classrooms, completed survey packs that examined their conceptualisations of citizenship and learning experiences through open‐ended questions and a diamond ranking exercise (Akar ).…”
Section: Researching Citizenship Education In Lebanonmentioning
confidence: 99%
See 1 more Smart Citation